Non-structural silicon-aluminum cementing material concrete as well as preparation method and application thereof

By optimizing the composition and preparation method in non-structural silicon-aluminum gelling material concrete, the problem of insufficient anti-freeze-thaw cycle performance of silicon-aluminum gelling material in non-structural concrete in the prior art is solved, and low carbon and low energy are achieved It is suitable for buildings in severe cold areas and promotes the resource utilization of red mud.

CN119161137APending Publication Date: 2024-12-20CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411294279.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art has insufficient research on low carbon emissions, low energy consumption and high performance in the application field of silicon-aluminum gelling materials, especially in the lack of effective solutions in the anti-freeze-thaw cycle performance of non-structural concrete.

Method used

The composition based on mass percentage is: 10% to 25% of the gelling component of silicon-aluminum gelling material, 0.5% to 1.4% of the auxiliary exciter, 36% to 50% of the crude aggregate, 25% to 40% of the fine aggregate % , 5.0% ~ 12.5% ​​water, 0% ~ 0.6% calcium lignin sulfonate, non-structural silicon-aluminum gelling material concrete is prepared evenly by grinding and stirring, and is suitable for concrete buildings in severe cold areas.

Benefits of technology

It provides excellent workingability and strength performance, and makes up for the application gap of red mud-based silicon-aluminum gelling materials prepared in non-structural concrete with low-cost, low-carbon emissions in the prior art. It has better anti-freeze-thaw circulation performance, suitable for buildings in severe cold areas, and promotes the resource utilization of red mud and the sustainable development of the alumina industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005045476490000061
    Figure BDA0005045476490000061
  • Figure BDA0005045476490000071
    Figure BDA0005045476490000071
  • Figure BDA0005045476490000072
    Figure BDA0005045476490000072
Patent Text Reader

Abstract

The invention relates to concrete for a non-structural silicon-aluminum cementing material as well as a preparation method and application of the concrete. The silicon-aluminum cementing material concrete is prepared from the following components in percentage by mass: 10%-25% of a silicon-aluminum cementing material cementing component, 0.5%-1.3% of an auxiliary exciting agent, 36%-50% of coarse aggregate, 25%-40% of fine aggregate, 5.0%-12.5% of water and 0%-0.6% of calcium lignosulphonate. Compared with Portland cement concrete, the silicon-aluminum cementing material concrete provided by the invention has more excellent freeze-thaw cycle resistance, and can be suitable for preparation of concrete buildings in severe cold areas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to concrete, in particular to non-structural silicon-aluminum cementitious material concrete and a preparation method and application thereof. Background Art

[0002] The cement industry is an important basic industry of the national economy and a key area of ​​energy consumption and carbon dioxide emissions. In 2011, my country's cement production exceeded 2 billion tons for the first time, and has remained at a high production level of more than 2 billion tons for more than ten years. Based on the calculation that carbon emissions per ton of cement are 550 kg, my country's cement industry has emitted more than 1.1 billion tons of carbon per year in the past decade, which has brought huge challenges to my country's energy conservation and emission reduction work.

[0003] The silicon-alumina cementitious material, which uses solid waste as the main raw material and does not require high-temperature calcination, is a new type of cementitious material with typical low-carbon characteristics. It has similar physical and chemical properties to traditional cementitious materials such as silicate cement, but its CO2 emissions are only 20% to 80% of the latter. In addition, the silicon-alumina cementitious material has unique properties that are superior to ordinary silicate cement, such as high strength, fast hardening, and acid and alkali corrosion resistance. At the same time, it has the advantages of abundant materials, simple process, low price, and energy saving, which has attracted great interest from domestic and foreign material experts.

[0004] To this end, the prior art discloses a silicon-alumina gelling material based on solid waste such as red mud and a preparation method thereof, which uses 10-60 parts of red mud, 20-70 parts of slag, and adds 0.1-8% of an auxiliary activator by weight to prepare a silicon-alumina gelling material with excellent strength performance at room temperature. However, this only focuses on the preparation of gelling materials, and there is still a lack of research on its application technology field.

[0005] Therefore, it is necessary to provide an application method for silicon-alumina cementitious materials with low carbon emissions, low energy consumption and high performance. Summary of the invention

[0006] In view of this, the main purpose of the present invention is to provide a non-structural silicon-alumina cementitious material concrete and its preparation method and application. The silicon-alumina cementitious material concrete has more excellent anti-freeze-thaw cycle performance and can be suitable for the preparation of concrete buildings in severe cold regions.

[0007] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical scheme. The present invention proposes a non-structural silicon-aluminum cementitious material concrete, which is composed of 10% to 25% of silicon-aluminum cementitious material cementitious component, 0.5% to 1.4% of auxiliary activator, 36% to 50% of coarse aggregate, 25% to 40% of fine aggregate, 5.0% to 12.5% ​​of water, and 0% to 0.6% of calcium lignin sulfonate.

[0008] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.

[0009] Preferably, in the aforementioned non-structural silica-alumina cementitious material concrete, the cementitious components of the silica-alumina cementitious material are composed by mass percentage of: 20-50% red mud; 50-80% slag powder.

[0010] Preferably, in the aforementioned non-structural silica-alumina cementitious material concrete, the auxiliary activator is sodium carbonate, which is calculated by the mass percentage of Na2O.

[0011] Preferably, in the aforementioned non-structural silica-alumina cementitious material concrete, the red mud is sintered red mud or Bayer red mud; and the slag powder is water-quenched slag powder or air-cooled granulated blast furnace slag powder.

[0012] Preferably, the aforementioned non-structural silicon-alumina cementitious material concrete, wherein the red mud comprises, by mass percentage: Al2O3 8.0% to 25%; SiO2 15.0% to 30%; Fe2O3

[0013] 5%~15%; CaO 5%~50%; MgO 0.1%~2%; K2O 0.001%~1%; Na2O 2%~8%; SO3≤5%, the sum of the mass percentages of the above components is 100%.

[0014] Preferably, in the aforementioned non-structural silicon-alumina cementitious material concrete, the slag powder has the following composition by mass percentage: CaO 30-45%; SiO2 20-38%; MgO 1-12%; Al2O3 10-30%; MnO 0-3%; Fe2O3 0-5%; SO3 0-5%, and the sum of the mass percentages of the above components is 100%.

[0015] Preferably, in the aforementioned non-structural silica-alumina cementitious material concrete, the coarse aggregate is crushed stone.

[0016] Preferably, in the aforementioned non-structural silicon-alumina cementitious material concrete, the particle size range of the coarse aggregate is 5-25 mm, and the mass ratio of aggregates with particle sizes of 5-10 mm to 10-25 mm is 5:5.

[0017] Preferably, in the aforementioned non-structural silicon-alumina cementitious material concrete, the fine aggregate is machine-made sand or river sand.

[0018] Preferably, in the aforementioned non-structural silica-alumina cementitious material concrete, the fineness modulus of the fine aggregate is 2.6, the mud content is less than 3.3wt%, and the crushing index is less than 16wt%.

[0019] Preferably, in the aforementioned non-structural silica-alumina cementitious material concrete, the auxiliary activators sodium carbonate and calcium lignin sulfonate are solid, and their solid content is 95-100wt%.

[0020] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a method for preparing non-structural silicon-alumina cementitious material concrete, comprising the following steps:

[0021] 1) grinding the gelling component of the silica-alumina gelling material to a 45 μm square hole sieve with a sieve residue of less than 12%;

[0022] 2) After the silica-alumina cementitious material cementitious components, the auxiliary activator sodium carbonate and calcium lignin sulfonate are uniformly stirred, fine aggregate and coarse aggregate are added and uniformly stirred, and then water is added and uniformly stirred again to obtain the silica-alumina cementitious material concrete.

[0023] The purpose of the present invention and the solution of its technical problems can be further achieved by adopting the following technical measures. A concrete product proposed by the present invention adopts a non-structural silicon-aluminum cementitious material concrete;

[0024] The composition of the non-structural silicon-aluminum cementitious material concrete in terms of mass percentage is: 10% to 25% of silicon-aluminum cementitious material cementitious component, 0.5% to 1.3% of auxiliary activator, 36% to 50% of coarse aggregate, 25% to 40% of fine aggregate, 5.0% to 12.5% ​​of water, and 0% to 0.6% of calcium lignin sulfonate.

[0025] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.

[0026] Preferably, the aforementioned concrete product is roadbed and pavement concrete, concrete bricks, concrete brick pipes, concrete bricks or concrete walls.

[0027] Compared with the prior art, the non-structural silicon-alumina cementitious material concrete and its preparation method and application described in the present invention have the following beneficial effects:

[0028] 1. The non-structural siliceous-aluminous cementitious concrete provided by the present invention has excellent workability and strength performance, which makes up for the blank of the application of red mud-based siliceous-aluminous cementitious materials prepared by using low-cost and low-carbon emission weak alkali sodium carbonate as an activator in non-structural concrete in the prior art, and is an effective expansion of the existing application technology field of siliceous-aluminous cementitious materials.

[0029] 2. Compared with silicate cement concrete, the silica-alumina cementitious material concrete provided by the present invention has more excellent anti-freeze-thaw cycle performance and can be used for the preparation of concrete buildings in severe cold regions.

[0030] 3. The cementitious material used in the silico-alumina cementitious material concrete described in the present invention is a silico-alumina cementitious material prepared with red mud, a solid waste discharged from the alumina industry, as the main raw material, which is beneficial to the resource utilization of red mud and the sustainable development of the alumina industry.

[0031] 4. The method for preparing non-structural silicon-alumina cementitious material concrete provided by the present invention is consistent with the existing method for preparing commercial concrete, does not require the purchase of new equipment, and has the characteristics of low cost, energy saving, low carbon and environmental protection.

[0032] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION

[0033] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a non-structural silicon-aluminum cementitious material concrete and its preparation method and application according to the present invention, its specific implementation method, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0034] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the usual meanings understood by ordinary technicians in the field to which the present invention belongs. If no specific experimental steps or conditions are specified below, the operations or conditions of the conventional experimental steps described in the literature in the field can be followed.

[0035] Some embodiments of the present invention provide a non-structural silica-alumina cementitious material concrete, which comprises, by mass percentage, 10% to 25% silica-alumina cementitious component, 0.5% to 1.4% auxiliary activator, 36% to 50% coarse aggregate, 25% to 40% fine aggregate, 5.0% to 12.5% ​​water, and 0% to 0.6% calcium lignin sulfonate.

[0036] In some embodiments, optionally, the composition of the silica-alumina cementitious material cementitious component by mass percentage is: 20-50% red mud; 50-80% slag powder. Preferably, the red mud accounts for 30-40% and the slag powder accounts for 60-70%. After such optimization, the strength of the silica-alumina cementitious material concrete used for non-structures is higher.

[0037] In some embodiments, optionally, the auxiliary activator is sodium carbonate, which is calculated as a mass percentage of Na2O.

[0038] In some embodiments, optionally, the red mud is sintered red mud or Bayer red mud, both of which are solid waste discharged from the alumina industry; and the slag powder is water-quenched slag powder or air-cooled granulated blast furnace slag powder.

[0039] In some embodiments, optionally, the red mud has the following composition by mass percentage: Al2O3 8.0% to 25%; SiO2 15.0% to 30%; Fe2O3 5% to 15%; CaO 5% to 50%; MgO0.1% to 2%; K2O 0.001% to 1%; Na2O 2% to 8%; SO3≤5%, and the sum of the mass percentages of the above components is 100%.

[0040] In some embodiments, optionally, the slag powder has a composition by mass percentage of: CaO 30-45%; SiO2 20-38%; MgO: 1-12%; Al2O3 10-30%; MnO 0-3%; Fe2O3 0-5%; SO3 0-5%, and the sum of the mass percentages of the above components is 100%.

[0041] In some embodiments, optionally, the coarse aggregate is crushed stone. Preferably, the coarse aggregate meets the continuous grading requirements and has a particle size range of 5-25 mm to form an optimal dense stacking state and improve the compressive strength of concrete.

[0042] In some embodiments, optionally, the fine aggregate is machine-made sand or river sand. Preferably, in order to ensure the workability, mechanical properties and durability of concrete, the fine aggregate has a fineness modulus of 2.6, a mud content of less than 3.3wt%, and a crushing index of less than 16%.

[0043] Some embodiments of the present invention also provide a method for preparing non-structural silicon-alumina cementitious material concrete, comprising the following steps:

[0044] 1) Drying the cementitious component of the silicon-alumina cementitious material, weighing it according to a proportion, mixing it, and grinding it until the residue on a 45 μm square hole sieve is less than 12%, thereby obtaining the cementitious component of the silicon-alumina cementitious material; the drying is drying to a constant weight at a temperature of 50 to 150° C.; if the residue on a 45 μm square hole sieve is greater than or equal to 12%, it indicates that the cementitious component is coarse, which will affect the strength development of the concrete.

[0045] 2) In a concrete mixer, the silica-alumina cementitious material cementitious component, the auxiliary activator sodium carbonate, and the calcium lignin sulfonate are added in order and stirred evenly, and then the fine aggregate and the coarse aggregate are added and stirred evenly, and then water is added and stirred evenly again to obtain the silica-alumina cementitious material concrete.

[0046] Some embodiments of the present invention further provide a concrete product, wherein the concrete product adopts the above-mentioned silicon-alumina cementitious material concrete for non-structures.

[0047] In some embodiments, optionally, the concrete product is roadbed and pavement concrete, concrete bricks, concrete brick pipes, concrete bricks or concrete walls. These are all non-structural engineering constructions, and can be maintained according to engineering needs.

[0048] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0049] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0050] Examples 1 to 16 respectively provide a non-structural silicon-alumina cementitious material concrete and a preparation method thereof. The proportions are shown in Table 1. The silicon-alumina cementitious material concrete of each example is prepared according to the following steps:

[0051] Weigh each component of the cementitious component, and after grinding, the residue of the cementitious component on a 45 μm negative pressure sieve is 7.2%; in a concrete mixer, add the silica-alumina cementitious component, the auxiliary activator sodium carbonate, and calcium lignin sulfonate in order and stir evenly, then add fine aggregate and coarse aggregate and stir evenly, then add water and stir evenly again to obtain the silica-alumina cementitious concrete.

[0052] The slump performance test of the prepared silicon-alumina cementitious material concrete was carried out with reference to GB / T 50080 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures". The test results are shown in Table 2.

[0053] The compressive strength test of the prepared silicon-alumina cementitious material concrete sample was carried out in accordance with GB / T 50081 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The test results are shown in Table 2.

[0054] The freeze-thaw cycle resistance test (quick freezing method) of the prepared silicon-aluminum cementitious concrete sample was carried out in accordance with GB / T 50082 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The test results are shown in Table 3.

[0055] Table 1 Proportion of silicon-alumina cementitious material concrete (wt%)

[0056]

[0057]

[0058] Among them, the red mud used in Examples 1-16 and Comparative Examples 1-7 is sintered red mud, and the slag is water-quenched slag powder, and their chemical compositions are shown in Tables 2 and 3.

[0059] Table 2 Chemical composition of red mud (wt%)

[0060]

[0061] Table 3 Chemical composition of slag powder (wt%)

[0062] materials CaO <![CDATA[SiO2]]> MgO <![CDATA[Al2O3]]> MnO <![CDATA[Fe2O3]]> <![CDATA[SO3]]> Slag powder 38.44 30.52 9.11 16.32 0.52 0.31 2.27

[0063] Table 4 Slump and compressive strength of silicon-alumina cementitious material concrete prepared in Examples 1-16 and Comparative Examples 1-7

[0064]

[0065]

[0066] From the data in Table 4, it can be seen that the slump of the silicon-aluminum cementitious material concrete prepared in Examples 1-16 of the present invention is 150-240 mm, the 3d compressive strength is 22.1-32.3 MPa, the 7d compressive strength is 25.5-38.6 MPa, and the 28d compressive strength is 30.9-55.5 MPa. This shows that the silicon-aluminum cementitious material concrete of the present invention has excellent workability and mechanical properties, and its strength can meet the requirements of C30, C40 and C50 grade concrete respectively. In addition, after the silica-alumina cementitious material cementitious component in the system of the present invention is mixed with water, a large amount of hydration products will be generated under the stimulation of the activator, and the aggregates of the concrete will be bonded to each other, thereby providing strength for the concrete. The higher its proportion, the higher the compressive strength of the concrete; but when it is higher than 25wt%, the concrete strength increment is not high, and when its content is lower than 10wt%, the concrete strength is too low, so its dosage range is selected to be 10wt% to 25w%; when the red mud content in the cementitious component is 30wt%-40wt%, the concrete strength is the highest; the auxiliary activator sodium carbonate provides alkalinity for the system to stimulate the depolymerization and condensation of SiO2, Al2O3 and CaO in the raw materials of the system, and accelerate the generation of hydration products; it can be seen from the data in Table 4 that too high or too low dosage of the auxiliary activator sodium carbonate leads to insufficient concrete strength, so the optimal dosage range of sodium carbonate (measured by the mass of Na2O) is 0.5wt% to 1.3wt%. In order to ensure the mechanical properties and workability of concrete, the proportion of coarse aggregate and fine aggregate is crucial. It can be seen from the examples and comparative examples that when the coarse aggregate is between 36wt% and 50wt% and the fine aggregate is between 25wt% and 40wt%, the 28d compressive strength of the concrete can reach the C30 grade. Calcium lignin sulfonate is mainly used to improve the workability of the concrete of the system. The addition of calcium lignin sulfonate reduces the interfacial tension between water and cementitious materials, making the cementitious material particles of the system disperse more evenly in water, thereby reducing the agglomeration between particles and significantly improving the slump of concrete. However, the workability of concrete is reduced when its addition amount exceeds 0.6wt%.

[0067] Since the strength of the silicon-alumina cementitious material concrete prepared in Comparative Examples 1-7 does not meet the standard, the following Table 5 does not test the durability (frost resistance) of the silicon-alumina cementitious material concrete prepared in Comparative Examples 1-7.

[0068] Table 5 Antifreeze properties of silicon-alumina cementitious material concrete prepared in Examples 1-16

[0069]

[0070]

[0071]

[0072]

[0073] Note: The control concrete described in the above table is a Portland cement concrete prepared with the same mix ratio using P·O 42.5R cement as the cementitious material. “-” means the sample has been damaged and no further testing is performed.

[0074] It can be seen from the data in Table 5 that the antifreeze ability of the silicon-aluminum cementitious material concrete prepared in Examples 1-16 of the present invention is better than that of ordinary Portland cement concrete. This is because the hydration product of ordinary Portland cement concrete is mainly calcium silicate hydrate (CSH gel), and the structural stability of the hydration product is poor during the freeze-thaw cycle, and it is easily damaged by repeated freeze-thaw of water, resulting in damage to the cement structure. The hydration product of silicon-aluminum cementitious materials is mostly sodium silicate hydrate, and the hydration products of these materials usually have higher chemical stability and physical stability, and can better resist the destructiveness of freeze-thaw cycles.

[0075] In the specification of the present invention, a lot of specific details are described. However, it is understood that embodiments of the present invention can be practiced without these specific details. In some embodiments, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this specification.

[0076] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0077] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

[0078] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A non-structural silicon-alumina cementitious material concrete, It is characterized in that The composition of the invention in terms of mass percentage is as follows: 10% to 25% of silica-alumina cementitious material cementitious component, 0.5% to 1.4% of auxiliary activator, 36% to 50% of coarse aggregate, 25% to 40% of fine aggregate, 5.0% to 12.5% ​​of water and 0% to 0.6% of calcium lignin sulfonate.

2. The non-structural silicon-alumina cementitious material concrete according to claim 1, It is characterized in that The gelling component of the silica-alumina gelling material is composed of 20-50% red mud and 50-80% slag powder in terms of mass percentage; the auxiliary activator is sodium carbonate, which is Na 2 O content in percent by mass.

3. The non-structural silicon-alumina cementitious material concrete according to claim 1, It is characterized in that The red mud is sintered red mud or Bayer red mud; the slag powder is water-quenched slag powder or air-cooled granulated blast furnace slag powder; the coarse aggregate is crushed stone; and the fine aggregate is machine-made sand or river sand.

4. The non-structural silicon-alumina cementitious material concrete as claimed in claim 3, It is characterized in that The red mud is composed of Al 2 O 3 8.0%~25%,SiO 2 15.0%~30%;Fe 2 O 3 5%~15%; CaO 5%~50%; MgO 0.1%~2%; K 2 O 0.001%~1%; Na 2 O 2%~8%; SO 3 ≤5%, the sum of the mass percentages of the above components is 100%; the composition of the slag powder in mass percentage is: CaO 30-45%; SiO 2 20~38%; MgO 1~12%; Al 2 O 3 10~30%; MnO 0~3%; Fe 2 O 3 0~5%; SO 3 0~5%, the sum of the mass percentages of the above components is 100%.

5. The non-structural silicon-alumina cementitious material concrete as claimed in claim 3, It is characterized in that The particle size range of the coarse aggregate is 5-25 mm, wherein the mass ratio of aggregates with particle sizes of 5-10 mm to 10-25 mm is 5:

5.

6. The non-structural silicon-alumina cementitious material concrete according to claim 3, It is characterized in that The fine aggregate has a fineness modulus of 2.6, a mud content of less than 3.3 wt %, and a crushing index of less than 16 wt %.

7. The non-structural silicon-alumina cementitious material concrete according to claim 1, It is characterized in that The auxiliary stimulants sodium carbonate and calcium lignin sulfonate are solid, and the solid content thereof is 95-100 wt %.

8. A method for preparing non-structural silicon-alumina cementitious material concrete, It is characterized in that The following steps are involved: 1) grinding the gelling component of the silica-alumina gelling material to a 45 μm square hole sieve with a sieve residue of less than 12%; 2) After the silica-alumina cementitious material cementitious components, the auxiliary activator sodium carbonate and calcium lignin sulfonate are uniformly stirred, fine aggregate and coarse aggregate are added and uniformly stirred, and then water is added and uniformly stirred again to obtain the silica-alumina cementitious material concrete.

9. A concrete product, It is characterized in that The concrete product adopts silicon-alumina cementitious material concrete for non-structure; The composition of the non-structural silicon-aluminum cementitious material concrete in terms of mass percentage is: 10% to 25% of silicon-aluminum cementitious material cementitious component, 0.5% to 1.25% of auxiliary activator, 40% to 50% of coarse aggregate, 25% to 40% of fine aggregate, 5.0% to 11.0% of water, and 0% to 0.6% of calcium lignin sulfonate.

10. The concrete product according to claim 9, It is characterized in that The concrete product is roadbed and pavement concrete, concrete bricks, concrete brick pipes, concrete bricks or concrete walls.

Citation Information

Cited By

  • Road concrete as well as preparation method and application thereof

    CN119707405A

  • Low-clinker cement-based concrete, decorative concrete member and application

    CN119797849A